THE CULTURAL CHARACTERISTICS OF INTERNATIONAL TOURISTS - I Putu Budiarta (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
Number of international tourists visiting Bali, Indonesia, keeps increasing. They usually come from different countries and cultural background. Objective of this research is to introduce some cultural characteristics of Chinese, Japanese, Korean, Australian, American, German, Indonesian, and Balinese. Data of this literature review was based on some academic books and electronic data from internet. Data was collected by reviewing some books and articles and by observing the characteristics of resident’s culture. The result showed that the culture of tourists and the culture of residents are very different. Japanese, Chinese, Korean, Indonesian, and Balinese prefer collectivism or group to individualism but, Australian, American, and Germany prefer individualism to collectivism. Indonesian and Balinese like asking about religion, age, salary, and possession but Australian, American, and Germany don’t like asking about them. It is recommended that all tourism employees should know about the tourist’s cultural aspects so that no misunderstanding between the tourists and the residents.